Rapid Serological Assays and SARS-CoV-2 Real-Time Polymerase Chain Reaction Assays for the Detection of SARS-CoV-2: Comparative Study - Paradiso, Angelo Virgilio; De Summa, Simona; Loconsole, Daniela; Procacci, Vito; Sallustio, Anna; Centrone, Francesca; Silvestris, Nicola; Cafagna, Vito; De Palma, Giuseppe; Tufaro, Antonio; Garrisi, Vito Michele; Chironna, Maria (JMIR Publications, 2020)
BackgroundReal-time polymerase chain reaction (RT-PCR) testing for the identification of viral nucleic acid is the current standard for the diagnosis of SARS-CoV-2 infection, but technical issues limit its utilization for large-scale screening. Serological immunoglobulin M (IgM)/IgG testing has been proposed as a useful tool for detecting SARS-CoV-2 exposure. ObjectiveThe objective of our study was to compare the results of the rapid serological VivaDiag test for SARS-CoV-2-related IgM/IgG detection with those of the standard RT-PCR laboratory test for identifying SARS-CoV-2 nucleic acid. MethodsWe simultaneously performed both serological and molecular tests with a consecutive series of 191 symptomatic patients. The results provided by a new rapid serological colorimetric test for analyzing IgM/IgG expression were compared with those of RT-PCR testing for SARS-CoV-2 detection. ResultsOf the 191 subjects, 70 (36.6%) tested positive for SARS-CoV-2 based on RT-PCR results, while 34 (17.3%) tested positive based on serological IgM/IgG expression. Additionally, 13 (6.8%) subjects tested positive based on serological test results, but also tested negative based on RT-PCR results. The rapid serological test had a sensitivity of 30% and a specificity of 89% compared to the standard RT-PCR assay. Interestingly, the performance of both assays improved 8 days after symptom appearance. After 10 days had passed since symptom appearance, the predictive value of the rapid serological test was higher than that of the standard molecular assay (proportion of positive results: 40% vs 20%). Multivariate analysis showed that age >58 years (P<.01) and period of >15 days after symptom onset (P<.02) were significant and independent factors associated with serological test positivity. ConclusionsThe rapid serological test analyzed in this study seems limited in terms of usefulness when diagnosing SARS-CoV-2 infection. However, it may be useful for providing relevant information on people's immunoreaction to COVID-19 exposure.